Microesferas de PCL como sistema de liberação controlada de herbicida glifosato - Holz, Juliana Pelisoli (2017)
Glyphosate is the most widely used herbicide in the world, due to its broad spectrum of action. But there is a need for reduction measures in its application, due to the risks associated with contamination of water and the environment. The development of controlled release systems appears as an alternative to minimize the application of this herbicide. This work aimed at the preparation of glyphosate-containing Poly (ε-caprolactone) (PCL) microspheres. These were characterized as to their morphology, structure, physicochemical properties, and a bioassay was carried out to evaluate their use in rice cultivation, in order to create a possible alternative for the use of these herbicides in plantations. The PCL / glyphosate microspheres produced by the multiple emulsion technique and solvent evaporation were in the form of solid beads with mean sizes of 3 μm ± 0.6 μm. It was possible to incorporate 9.3% glyphosate in relation to the polymer mass in the formed particles, revealing an efficiency of incorporation IE of 30.9%. From the techniques used to quantify the incorporated glyphosate (UVvis, TGA and CHN), it can be stated that with the increase of glyphosate concentration in the formulation there is an increase in its IE. On the other hand, this increase leads to a decrease in the average size of the microspheres. The release of the herbicide from the microspheres was evidenced by bioassays, and in the assessment of the glyphosate release profile of the microspheres, it can be seen that approximately 17% of the herbicide was released into the medium, 0.01 M CaCl2 solution at room temperature, after 360 minutes of testing. This study allowed to affirm that the theoretical model described by Korsmeyer-Peppas is adequate to characterize the phenomenon of transport of glyphosate release from the microspheres, revealing an anomalous transport not governed by Fick diffusion.